Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.9734/ajrimps/2021/v10i130156
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ABO and Rhesus Blood Group on Blood Pressure and Hypertension in Bayelsa State

Abstract: Aim: This present study was carried out to ascertain the influences of ABO and Rhesus blood groups on blood pressure and hypertension among normotensive and hypertensive patients attending cardiologic clinic in Niger delta University Teaching Hospital, Okolobiri in Yenagoa Local Government Area of Bayelsa State Nigeria. Study Design: Cross sectional study design was adopted. Place and Duration of Study: The study was carried out in the Cardiology Clinics in the Niger Delta University Teaching Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Similarly, the most common Rh -ve blood group in both pre-and post-menopausal women was O-. Comparable findings were reported by both Kaur, Maninder, 2014 and Ojeka, S, et al, 2021, suggesting that individuals possessing blood type O might have a heightened vulnerability to developing hypertension [13,23]. However, some observations have contradicted this notion and indicated that blood type B was predominant among individuals with hypertension [12.…”
Section: Disscusionmentioning
confidence: 88%
“…Similarly, the most common Rh -ve blood group in both pre-and post-menopausal women was O-. Comparable findings were reported by both Kaur, Maninder, 2014 and Ojeka, S, et al, 2021, suggesting that individuals possessing blood type O might have a heightened vulnerability to developing hypertension [13,23]. However, some observations have contradicted this notion and indicated that blood type B was predominant among individuals with hypertension [12.…”
Section: Disscusionmentioning
confidence: 88%